Distributed Real-Time Multimedia Databases - Stančić, Hrvoje (2000)
In this paper the author considers issues in the development of the distributed real-time multimedia databases. He defines real-time databases and analyses a number of requirements such a database should comply to. In the end the author determines the important role of interactivity and multimedia as the key concepts of recent database developments.
Projekt MZOS
ENG